An Analysis of the Tourist Mobility in the Island of Lanzarote: Car Rental Versus More Sustainable Transportation Alternatives - Martín Martín, José María; Guaita Martínez, José Manuel; Molina Moreno, Valentín; Sartal Rodríguez, Antonio (Sustainability, 2019)
Studies have shown that certain modes of tourist development jeopardize the environment, as in the case of mass tourism, especially in areas that require special protection. The goal of this study is to apply a proposal for studying sustainability of tourist mobility to a protected space, the island of Lanzarote, which has been declared a Biosphere Reserve by UNESCO. This paper seeks to figure out the mobility patterns of tourists, the criterion used to select a mode of transportation, the attitude of tourists towards the sustainability of transport, and its environmental implications by analyzing secondary sources and interviewing tourists. The results show that the tourism model of the island is based on scattered natural resources that tourists want to enjoy in a tailor-made visit, which makes it hard to give up individual transportation. The only environmentally sustainable alternative is opting for electric vehicles with charging stations in the aforementioned tourist spots.
Keywords: mobility; sustainable development; environmental sustainability; Scopus; JCR